Quantum Physics Education Research over the Last Two Decades: A Bibliometric Analysis - Philipp Bitzenbauer (MDPI AG, 2021)
Quantum physics is an essential field of science education research, which reflects the high relevance of research on quantum physics and its technologies all around the globe. In this paper, we report on a bibliometric analysis of the science education research community’s scientific output in the area of quantum physics in the period from 2000 to 2021. A total of 1520 articles published in peer-reviewed physics and science education journals were retrieved from Web of Science and Scopus databases to conduct bibliometric analysis. This study aims to provide an overview of quantum physics education research in terms of scientific production, preferred publication venues, most involved researchers and countries (including collaborations), and research topics. The main findings point to a continuous increase in research output in the field of quantum physics education over the last two decades. Furthermore, they indicate a shift regarding the research foci. While formerly mainly papers on the teaching of quantum physics content were published, recently, an increase in the relevancy of empirical studies on the teaching and learning of quantum physics can be observed.